Bedside tracer gas technique accurately predicts outcome in aspiration of spontaneous pneumothorax. Issue 8 (1st August 2001) - Kiely, D G; Ansari, S; Davey, W A; Mahadevan, V; Taylor, G J; Seaton, D
Abstract : BACKGROUND: There is no technique in general use that reliably predicts the outcome of manual aspiration of spontaneous pneumothorax. We have hypothesised that the absence of a pleural leak at the time of aspiration will identify a group of patients in whom immediate discharge is unlikely to be complicated by early lung re-collapse and have tested this hypothesis by using a simple bedside tracer gas technique. METHODS: Eighty four episodes of primary spontaneous pneumothorax and 35 episodes of secondary spontaneous pneumothorax were studied prospectively. Patients breathed air containing a tracer (propellant gas from a pressurised metered dose inhaler) while the pneumothorax was aspirated percutaneously. Tracer gas in the aspirate was detected at the bedside using a portable flame ioniser and episodes were categorised as tracer gas positive (>1 part per million of tracer gas) or negative. The presence of tracer gas was taken to imply a persistent pleural leak. Failure of manual aspiration and the need for a further intervention was based on chest radiographic appearances showing either failure of the lung to re-expand or re-collapse following initial re-expansion. RESULTS: A negative tracer gas test alone implied that manual aspiration would be successful in the treatment of 93% of episodes of primary spontaneous pneumothorax (p<0.001) and in 86% of episodes of secondary spontaneous pneumothorax (p=0.01). A positive test implied that manual aspiration would either fail to re-expand the lung or that early re-collapse would occur despite initial re-expansion in 66% of episodes of primary spontaneous pneumothorax and 71% of episodes of secondary spontaneous pneumothorax. Lung re-inflation on the chest radiograph taken immediately after aspiration was a poor predictor of successful aspiration, with lung re-collapse occurring in 34% of episodes by the following day such that a further intervention was required. CONCLUSIONS: National guidelines currently recommend immediate discharge of patients with primary spontaneous pneumothorax based primarily on the outcome of the post-aspiration chest radiograph which we have shown to be a poor predictor of early lung re-collapse. Using a simple bedside test in combination with the post-aspiration chest radiograph, we can predict with high accuracy the success of aspiration in achieving sustained lung re-inflation, thereby identifying patients with primary spontaneous pneumothorax who can be safely and immediately discharged home and those who should be observed overnight because of a significant risk of re-collapse, with an estimated re-admission rate of 1%.